A Linguistic and Historical Analysis of Sacrificial Offerings Presented to a Deity in the Old Greek Version of Sirach - Beckman, Peter (Université Saint-Paul / Saint Paul University, 2022)
Sirach is a Hebrew-language Jewish religious text that was likely written between 195-175 BC; it was later translated into Greek in Egypt after 132 BC. This investigation studies statements found in Greek Sirach about offerings presented to a deity within the book’s polytheistic historical and social context, namely, late 2nd century BC Ptolemaic Egypt. In chapter 1 I introduce the subject of my study which is the presentation of an offering to a recipient in the Greek version. I then introduce the state of the question of cultic imagery in Sirach. My study contributes to new information to this field in three major ways: (a) my study highlights the unique message and of the Greek version in its historical context of Ptolemaic Egypt, (b) my use of lexical semantics reproducibly links lexemes that participate in the same semantic field of offerings or sacrifices presented to a recipient (which in most cases was a deity), and (c) I employ some of the linguistic categories of Systemic Functional Linguistics (SFL) to organize my historical study which includes the imposition of repeatable exegetical questions to each passage. This approach provides new grammatically informed information about the authoritative interpersonal relationship between the teaching sage and his reader. In chapter 2 I introduce the method of my study which includes two linguistic tools of lexical semantics and Systemic Functional Linguistics. SFL will provide me with a linguistic rubric by which I can organize historical and linguistic information about my investigation. First, SFL provides me with the impetus to examine the historical environment which contributes to Sirach’s context of culture (this will be chapter 3). Second, a lexical semantic componential analysis will allow me to reproducibly highlight lexemes that share a semantic field of offerings provided to a recipient in Sirach itself (this will be in chapter 4). Third, once I have identified passages in Greek Sirach that contain sacrificial statements, I will engage in a historical-exegetical examination of these passages that is informed by the linguistic rubric of a SFL register. This study will include aspects of a text that contribute to Sirach’s context of situation (i.e. field, tenor, mode) and metafunctions (this will be in chapter 4). These tools will work together to guide my analysis while outlining linguistic and historical observations. The semantic goal of my study will be to understand the meaning of offerings presented to a recipient in the context of Ptolemaic Egypt from a semantic perspective. In chapter 3 I examine Greek Sirach’s statements about offerings presented to a deity within its polytheistic historical and social context of Ptolemaic Egypt after 132 BC. This social and cultic environment is part of SFL’s context of culture which will contribute to the field, tenor, and mode of Sirach. The context of culture is the historical world within which linguistic features occurred and can be observed. This information will describe the polytheistic context of Ptolemaic Jews which will inform why and for what purpose a book like Sirach was used. The Jewish community was a numerical minority that was surrounded by demotic and non-Jewish Greek culture. Some of their primary distinctives were their exclusive monotheism and exclusive material cult offerings to the God of Israel in the Jerusalem Temple. This exclusive religion clashed with the surrounding inclusive and polytheistic demotic and non-Jewish Greek religion that provided offerings to multiple deities in ubiquitous shrines and temples. Because of this social context, in order to combat assimilationist and syncretistic trends, traditional monotheistic Jews needed to affirm traditional exclusive monotheistic Jewish religion and cultic practices. They maintained and formed their community through educational and societal formation. This paideia-formation occurred in prayer-houses and through the instruction of their youth. Jewish religious communities used texts like Sirach to instruct young Greek-speaking upper-class youths in the practical embodiment of Jewish religion. As such, the religious context of Ptolemaic Egypt provides a crucial societal backdrop of Sirach’s cultic statements. Attention to the social and cultic context of contemporary Ptolemaic Egypt allows me to see how the cultic teachings in Sirach may have functioned to shape and reinforce exclusive monotheistic cultic practice in a given historical moment. In chapter 4 I analyze the text of Greek Sirach by applying carefully chosen linguistic tools. First, I identify historical features of Sirach that contribute to SFL’s situational elements. I identify aspects of the field, tenor, and mode of the book. An important new observation is that the linguistic and historical aspects of the book created an authoritarian environment of learning and submission between the teaching sage and his student/reader. First I use a lexical semantic componential analysis to identify lexemes that share a semantic field of an offering or sacrifice. Then, I narrow my analysis to only include lexemes that explicitly highlight a recipient of an offering in its immediate context. This analysis permits me to narrow my study to nine passages in Greek Sirach. Finally, I analyze nine passages that describe offerings presented to a recipient. I do so using a historical-exegetical analysis indebted to the linguistic categories of SFL. I identify aspects of each passage that contribute to their ideational and interpersonal meanings. The analysis of these nine passages reveals information about the sage’s portrayal of these offerings. There are only three possible recipients of offerings: the God of Israel, idols, and priests who are given a portion of an offering that was first offered to God. The sage only describes offerings that are potentially acceptable or successful as those which a worshiper presents to the God of Israel. The presentation of offerings to other deities is pointless because they are impotent gods and cannot receive an offering. This emphasis or absence of mention reveals the sage’s belief that offerings ought only to be presented to the God of Israel. The sage notes that the God of Israel can accept or reject an offering. The offeror must accompany an offering with a consistent moral lifestyle so that God accepts it. The sage mentions both material offerings as well as offerings of piety such as repentance or a thanksgiving offering. The sage also states that the purpose of an offering is to acquire forgiveness, create a memory before God, as well as to receive reciprocal benefit from God. In chapter 5, my study provides a synthesis of conclusions as well as some potential theological implications arising from the conclusions. Within the polytheistic context of the Jewish community in Ptolemaic Egypt, Sirach’s teaching instructed and formed an uncompromising cultic worldview for elite Ptolemaic Jewish youths. Since many of the sage’s students might have assimilated or been tempted to assimilate cultic beliefs from their demotic and Greek neighbours, they might also easily have jettisoned certain exclusivist cultic practices for the sake of acceptance, social harmony, and personal advancement in Ptolemaic culture. The authoritarian sage instructs his students in the correct Jewish religion. The sage thus reinforces the exclusivist Jewish monotheistic religious identity which separated his readers from their polytheistic neighbours. He enjoins both the importance of Jerusalem's cultic worship as well as the ability to participate in offerings of piety that could be performed in the Diaspora. This study concludes with some theological implications that arise from the conclusions. Sirach provides a witness for how theological leaders and texts engaged in the spiritual and theological formation of their readers/students in multicultural environments. Early Christians employed similar forms of engagement as they taught their students faithfully to emulate the instruction and way of life of the God of Israel in a pluralistic society. Sirach’s cultic teaching was itself used to inform the social and theological environment of early Christians, thus providing them with guidance in adhering to exclusivist monotheistic beliefs and cultic practices, providing offerings of piety mediated through the cultic system oriented toward and around their high priest Jesus, and encouraging a consistent moral life to present pleasing offerings.
Keywords: Sirach; Ecclesiasticus; Bible; Scripture; Old Testament; Theology; Second Temple Judaism; Ben Sira; Linguistics; Lexical Semantics; Systemic Functional Linguistics; Greek Sirach; Ptolemaic Egypt; Offerings; Sacrifices; Monotheism; Catholic Interpretation; Evangelical Interpretation; Exclusive Worship